AGAMA DALAM PERADABAN BARAT: SEKULARISME DAN NIHILIASASI KONSEP TUHAN - Fakih Hamdani (Journal of International Multidisciplinary Research, 2024)
Religion is an important element in human life, because humans in their creation were intentionally limited in form, so they depend on the Almighty Unlimited. The West, as one of the great forms of human civilization, has experienced various phases of periodization with various upheavals of thought and action regarding religion. The early western period with philosophy as the main reference made religion something that was put aside, the middle period of the western dark ages became very radical in religion which was dominated by the church, while in the final period religion was again put aside with the growth of philosophical culture. Philosophical culture in western civilization, in the author's analysis of various sources, has actually produced various forms of thought and action in western society towards religion, the most important of which is secularism and the nihilization of the concept of God. Secularism is a form of effort to eliminate religion in the context of western civilization, in line with the development of thought with efforts to nihilize the concept of God and the scientific culture of western society. Agama menjadi salah satu unsur yang penting dalam kehidupan manusia, sebab manusia dalam penciptaannya memang disengaja dalam bentuk terbatas, sehingga tergantung kepada Dzat yang Maha tidak terbatas. Barat, sebagai salah satu wujud peradabaan besar umat manusia telah mengalami berbagai fase periodesasi dengan berbagai pergolakan pemikiran dan aksi terhadap agama. Periode awal barat dengan filsafat sebagai acuan utama menjadikan agama sebagai hal yang dikesampingkan, periode pertengahan abad kegelapan barat menjadi sangat radikal dalam beragama yang didominasi oleh gereja, sedangkan dalam periode akhir agama kembali dikesampingkan dengan tumbuh berkembangnya budaya filsafat. Budaya filsafat dalam peradaban barat, dalam penelahaan penulis dari berbagai sumber nyata-nyata telah menghasilkan berbagai bentuk pemikiran dan aksi masyarakat barat terhadap agama, yang paling utama adalah sekularisme dan nihilisasi konsep tuhan. Sekularisme yang merupakan bentuk upaya menghilangkan agama dalam konteks kehidupan peradaban barat, seiring sejalan dengan perkembangan pemikiran dengan upaya nihilisasi konsep Tuhan dan budaya keilmuan masyarakat barat.